Application of different doses of compost as a substitution of the commercial substrate in nursery for pepper and tomato seedlings - Maria Fiasconaro; Mariana Abrile; Lucia Hintermeister; Maria del Carmen Antolin; Maria Eugenia Lovato (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The decreasing number of peatlands has driven the search for new cultivation substrates. The aim of this study was to evaluate the use of different composts as growing media in the production of vegetable seedlings (pepper and tomato).Method Composts were produced from: discarded carrots (ZC), fats (FC), and biosolids (BC) from the dairy industry. They were used as peat substitutes in different doses depending on the germinating species: control (CS-commercial substrate) and three growing media prepared with perlite: 25, 35, and 45% of ZC, FC, and BC for pepper seedlings and 40, 55 and 70% of ZC, FC, and BC for tomato seedlings. When the plants were ready for transplantation they were harvested and the data were collected to assess the development of the seedlings in the different growth media.Results The obtained results suggest the possibility of total substitution of the CS by ZC, FC, and BC to produce pepper and tomato plants in commercial nurseries. The plants cultivated with composts presented higher concentrations of total dry matter compared to the controls. Photosynthetic pigments were affected by the presence of FC and BC, whereas TSP concentration was favored by BC.Conclusion Ours results suggest that it is feasible to perform a total substitution of commercial substrates with composts of different origins and compositions for the production of pepper and tomato plants in commercial nurseries.